Postpartum physical intimate partner violence among women in rural Zambia. Issue 2 (5th September 2018) - Munro‐Kramer, Michelle L.; Scott, Nancy; Boyd, Carol J.; Veliz, Philip T.; Murray, Sarah M.; Musonda, Gertrude; Lori, Jody R.
Abstract: Objective: To examine the demographic characteristics and mental health of women in rural Zambia who experienced physical intimate partner violence (IPV) postpartum. Methods: The present secondary analysis was conducted using baseline data from an impact evaluation of a maternity waiting home intervention in rural Zambia. A quantitative household survey was conducted over 6 weeks, from mid‐April to late May, 2016, at 40 rural health facility catchment areas among 2381 postpartum women (13 months after delivery; age ≥15 years). Results: A total of 192 (8.1%) women reported experiencing any type of physical IPV in the preceding 2 weeks; 126 had experienced severe physical IPV (had been kicked, dragged, beat, and/or choked by a husband or partner). High levels of depression were recorded for 174 (7.3%) women in the preceding 2 weeks. Being a female head of household was associated with an increased likelihood of experiencing severe physical IPV (aOR 2.64, 95% CI 1.70–4.10). Women with high depression scores were also at an increased risk of experiencing any physical IPV (aOR 17.1, 95% CI 8.44–34.9) and severe physical IPV (aOR 15.4, 95% CI 5.17–45.9). Conclusion: Future work should consider the implications of government and educational policies that could impact the screening and treatment of pregnant women affected by all forms of physical IPV and depression in rural Zambia. Abstract : Postpartum physical intimate partner violence among women in rural Zambia was associated with being a female head of household and high levels of depression.